The Jetty Dwellers Of Penang : Incorporation And Marginalisation Of An Urban Clan Community - Chan, Lean Heng (1980)
This study represents an attempt to analyze at the micro-level the process of socio-economic change in an urban poor community within a metropolitan centre in the Third World. The community chosan — the Chew Jetty settlement in Georgetown, Penang Island, Malaysia - is a waterfront settlement created about a century ago by Chinese migrants sharing a common geographical, historical and lineage origin. Using the world-system approach as a theoretical framework and employing a combination of social research techniques, the study seeks to reconstruct the historical transformation of the jetty community's internal socio-economic structure and the dynamics of its adaptive responses to external changes.